Open Access and Promotion and Tenure Evaluation Plans at the University of Wisconsin–Eau Claire. Issue 2 (3rd April 2017) - Wical, Stephanie H.; Kocken, Gregory J.
ABSTRACT: Department and program evaluation plans at the University of Wisconsin–Eau Claire were examined to see if these documents provide evidence that could be used to justify supporting the publication of peer-reviewed open access articles toward tenure and promotion. In an earlier study, the authors reveal that faculty members at the University of Wisconsin–Eau Claire are more unaware of open access publishing than their counterparts at larger universities. These findings dovetail with other studies that show that faculty members are reluctant to publish in open access journals because of concerns about the quality of those journals. The existing body of scholarship suggests that tenure-line faculty fear publishing in open access journals because it could adversely impact their chances of promotion and tenure. The authors of this current study sought to determine if department and program evaluation plans could influence negative perceptions faculty have of open access journals. The implications of this study for librarians, scholarly communication professionals, tenure-line faculty, departments, and programs are addressed.